Comparison of Monte Carlo and analytical dose computations for intensity modulated proton therapy. (9th February 2018) - Yepes, Pablo; Adair, Antony; Grosshans, David; Mirkovic, Dragan; Poenisch, Falk; Titt, Uwe; Wang, Qianxia; Mohan, Radhe
Abstract: To evaluate the effect of approximations in clinical analytical calculations performed by a treatment planning system (TPS) on dosimetric indices in intensity modulated proton therapy. TPS calculated dose distributions were compared with dose distributions as estimated by Monte Carlo (MC) simulations, calculated with the fast dose calculator (FDC) a system previously benchmarked to full MC. This study analyzed a total of 525 patients for four treatment sites (brain, head-and-neck, thorax and prostate). Dosimetric indices (D02, D05, D20, D50, D95, D98, EUD and Mean Dose) and a gamma-index analysis were utilized to evaluate the differences. The gamma-index passing rates for a 3%/3 mm criterion for voxels with a dose larger than 10% of the maximum dose had a median larger than 98% for all sites. The median difference for all dosimetric indices for target volumes was less than 2% for all cases. However, differences for target volumes as large as 10% were found for 2% of the thoracic patients. For organs at risk (OARs), the median absolute dose difference was smaller than 2 Gy for all indices and cohorts. However, absolute dose differences as large as 10 Gy were found for some small volume organs in brain and head-and-neck patients. This analysis concludes that for a fraction of the patients studied, TPS may overestimate the dose in the target by as much as 10%, while for some OARs the dose could be underestimated by as much as 10 Gy. Monte Carlo dose calculations may be needed to ensure more accurate dose computations to improve target coverage and sparing of OARs in proton therapy.